2012
DOI: 10.1136/gutjnl-2012-303090
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive functional analysis of chymotrypsin C (CTRC) variants reveals distinct loss-of-function mechanisms associated with pancreatitis risk

Abstract: Objective The digestive enzyme chymotrypsin C (CTRC) protects against pancreatitis by promoting degradation of trypsinogen and thereby curtailing potentially harmful trypsinogen activation. Loss-of-function variants in CTRC increase the risk for chronic pancreatitis. The aim of the present study was to perform comprehensive functional analysis of all missense CTRC variants identified to date. Design We investigated secretion, activity and degradation of 27 published and 5 novel CTRC mutants. We also assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 18 publications
5
91
0
Order By: Relevance
“…Thus, high-penetrance PRSS1 variants cause higher trypsin levels either by stimulating trypsinogen autoactivation and/or by inhibiting CTRC-dependent trypsinogen degradation (13,33). Loss-of-function mutations in the protective trypsin inhibitor SPINK1 or the trypsinogen-degrading enzyme CTRC can also result in elevated trypsin activity (1,4,5,15,18,26). Consistent with the trypsin paradigm, a rapidly autodegrading variant of PRSS2 encoding human anionic trypsinogen was shown to protect against chronic pancreatitis (47).…”
mentioning
confidence: 67%
“…Thus, high-penetrance PRSS1 variants cause higher trypsin levels either by stimulating trypsinogen autoactivation and/or by inhibiting CTRC-dependent trypsinogen degradation (13,33). Loss-of-function mutations in the protective trypsin inhibitor SPINK1 or the trypsinogen-degrading enzyme CTRC can also result in elevated trypsin activity (1,4,5,15,18,26). Consistent with the trypsin paradigm, a rapidly autodegrading variant of PRSS2 encoding human anionic trypsinogen was shown to protect against chronic pancreatitis (47).…”
mentioning
confidence: 67%
“…CPA1 had no detectable effect on trypsinogen activation, trypsin activity or trypsinogen degradation by CTRC, indicating that CPA1 variants do not exert their effect via increasing the intrapancreatic trypsin activity. On the other hand, most of the loss-of-function CPA1 variants exhibit markedly reduced secretion, raising the possibility that CPA1 variants undergo misfolding in the ER and cause ER stress, as demonstrated previously for some PRSS1 and CTRC mutants (Kereszturi et al 2009b;Beer et al 2013). Indeed, the expression of p.N256K variant in AR42J rat pancreatic acinar cells resulted in ER stress, as evidenced by increased splicing of X-box binding protein 1 and elevated mRNA levels of the chaperons BiP and calreticulin.…”
Section: Cpa1 Variantsmentioning
confidence: 98%
“…It has been reported that the CTRC variants in exons 3 and 7 are associated with CP in Europe and India (Rosendahl et al 2008;Masson et al 2008;Beer et al 2013;Paliwal et al 2013). In European cohorts, the micro-deletion variants p.K247_R254del (c.738_761del24) and p.R254W, both located in exon 7, are the most common CTRC variants (Rosendahl et al 2008;Masson et al 2008;Beer et al 2013). In India, these variants are rare, and the p.A73T (c.217G>A) variant in exon 3 and the p.V251I (c.703G>A) variant in exon 7 are the most common ones (Rosendahl et al 2008;Paliwal et al 2013).…”
Section: Ctrc Variantsmentioning
confidence: 99%
“…Loss-offunction mutations in chymotrypsinogen C (CTRC) and the serine protease inhibitor, Kazaltype 1 (SPINK1) reduce the protective functions of these trypsin inhibitors in the pancreas (7,52,68,84).…”
Section: Other Genesmentioning
confidence: 99%